Method for producing porous material

JP2025507125APending Publication Date: 2025-03-13AIRGEL-IT GMBH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024553632
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-08
Filing Date
2023-03-08
Publication Date
2025-03-13

Smart Images

  • Figure 2025507125000001
    Figure 2025507125000001
  • Figure 2025507125000002
    Figure 2025507125000002
  • Figure 2025507125000003
    Figure 2025507125000003
Patent Text Reader

Abstract

The present invention relates to a method for preparing a porous material, comprising the steps of providing a mixture (M1) comprising at least a water-soluble bio-based polyphenol polymer selected from the group consisting of lignin biopolymers and tannin biopolymers as compound (C1) and water, contacting the mixture (M1) with an aqueous solution of at least one polyvalent metal ion to prepare a gel (A), exposing the gel (A) obtained to a water-miscible solvent (L) to obtain a gel (B) and drying the gel (B). The present invention further relates to the porous material thus obtained and the use of this porous material as a thermal insulation material, as a carrier material for the loading and release of active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in household appliances, in building and construction applications, in home and commercial appliance applications, in temperature control logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetics applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for preparing a porous material, comprising the steps of providing a mixture (M1) comprising at least a water-soluble bio-based polyphenol polymer selected from the group consisting of lignin biopolymers and tannin biopolymers as compound (C1) and water, contacting the mixture (M1) with an aqueous solution of at least one polyvalent metal ion to prepare a gel (A), exposing the gel (A) obtained to a water-miscible solvent (L) to obtain a gel (B) and drying the gel (B). The present invention further relates to the porous material thus obtained and the use of this porous material as a thermal insulation material, as a carrier material for the loading and release of active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in household appliances, in building and construction applications, in home and commercial appliance applications, in temperature control logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetics applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

[0002] Porous materials based on bio-based polymers, such as polymer foams, with pore sizes in the range of a few microns or less and high porosity of at least 70% are particularly suitable for a variety of applications.

[0003] Such porous materials with small average pore size can be in the form of organic aerogels or xerogels, for example, produced by a sol-gel process and then dried. In the sol-gel process, a sol based on an organic gel precursor is first produced, which is then gelled to form a gel by a crosslinking step. To obtain a porous material, for example an aerogel, from the gel, the liquid must be removed. In the following, this step will be referred to as drying for simplicity.

[0004] The present invention relates to a method for producing a porous material containing a bio-based phenolic polymer, and such a porous material and its use. In particular, the present invention relates to a method for producing a lignin-containing porous material. Lignin is a heterogeneous biopolymer. Depending on its origin, e.g. wood and / or plant source, and the extraction method, it may differ in properties such as molar mass or degree of condensation, and in chemical composition. Typically, lignin is a disordered biopolymer with three main building blocks, namely coumaryl alcohol, coniferyl alcohol, and sinapyl alcohol. Other suitable bio-based phenolic polymers are, for example, tannins. Tannins, which may be natural products found in bark and other biological sources, are polymeric polyphenolic compounds containing hydroxyl and other functional groups. There are several classes of tannins, which generally differ in their base or monomer units.

[0005] In principle, porous materials based on biobased phenolic polymers are known in the art, for example based on lignin and / or tannin or mixtures of lignin with other polymers. Methods for the preparation of lignin-based aerogels are also known in the art.

[0006] Several processes have been disclosed in the scientific literature. For example, an article in the Journal of Supercritical Fluids, 2015, 105, 1-8, describes a process for the preparation of hybrid alginate and lignin aerogels using pressurized carbon dioxide for gelation. When an alkaline aqueous solution of alginate and lignin containing calcium carbonate was exposed to CO2, a hydrogel was formed.

[0007] US02010329208A1 discloses a method for producing high-purity lignin-based carbon aerogel.

[0008] Highly porous organic aerogels based on tannin and lignin are disclosed in "New Tannin-Lignin Aerogels", Grishechko, L. et al., Industrial Crops and Products, 2013, 41, 347-355. The hydrogels described are prepared at constant solids content and constant pH, but with different mass ratios of tannin / lignin and (tannin+lignin) / formaldehyde.

[0009] Generally, organic molecules such as isocyanates or aldehydes are used as crosslinking agents. In many applications, these compounds are disadvantageous because they are often hazardous and may remain in trace amounts in the resulting material. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] US02010329208A1 [Non-patent literature]

[0011] [Non-Patent Document 1] Journal of Supercritical Fluids,2015,105,1-8 [Non-Patent Document 2] "New Tannin-Lignin Aerogels", Grishechko, L. et al., Industrial Crops and Products, 2013, 41, 347-355 Summary of the Invention [Problem to be solved by the invention]

[0012] Therefore, the object of the present invention was to avoid the above-mentioned drawbacks. One object of the present invention was to provide a method for preparing a porous material based on polyphenol polymers, which avoids harmful substances. A further object of the present invention was to provide a porous material suitable for use as thermal insulation, as a carrier material for loading and releasing active agents, for battery applications, as electrode material for batteries, fuel cells or electrolysis, for catalysis, for capacitors, for home appliances, for building and construction applications, for home appliance applications, for temperature control logistics applications, for vacuum insulation applications, for clothing applications, for food applications, for cosmetics applications, for biomedical applications, for agricultural applications, for consumer applications, for packaging applications or for pharmaceutical applications.

[0013] The porous material should preferably have a high surface area.Furthermore, it was an object of the present invention to provide a method for preparing a homogenous gel, and consequently a homogenous porous material, from bio-based polyphenolic polymers such as lignin or tannin or mixtures thereof. [Means for solving the problem]

[0014] According to the invention, this object is achieved by at least the following steps: a) providing a mixture (M1) comprising a water-soluble bio-based polyphenol polymer selected from the group consisting of lignin biopolymers and tannin biopolymers as compound (C1), and water; b) contacting the mixture (M1) with an aqueous solution of at least one polyvalent metal ion to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); The problem is solved by a method for preparing a porous material, comprising: DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] According to a further embodiment, the present invention relates to a method for producing a pharmaceutical composition comprising at least the following steps: a) providing a mixture (M1) comprising a water-soluble bio-based polyphenol polymer selected from the group consisting of lignin biopolymers and tannin biopolymers as compound (C1), and water; b) contacting the mixture (M1) with an aqueous solution of at least one polyvalent metal ion to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); The present invention also relates to a method for preparing a porous material, comprising: Here, the mixture (M1) further comprises, as compound (C2), at least one water-soluble polysaccharide having carboxylic acid groups.

[0016] According to the present invention, water-soluble bio-based polyphenol polymers are used to form the gel. Suitable phenol polymers are in principle known from the art. In the context of the present invention, lignin and tannin are preferably used as bio-based polymers due to the good availability of starting materials. The use of lignin, tannin and / or their derivatives and / or their mixtures is particularly attractive due to their stability, availability, renewability and low toxicity.

[0017] Moreover, according to a further aspect of the present invention, biobased polymers, inorganic precursors, and polysaccharides with carboxylic acid groups are used to form the gel. Suitable biobased polymers, inorganic precursors, and polysaccharides with carboxylic acid groups are in principle known from the art. Suitable polysaccharides with carboxylic acid groups are, for example, alginates, pectins, modified cellulose, xanthan, hyaluronic acid, or modified starches. The use of these biobased polymers and polysaccharides and their derivatives is particularly attractive due to their stability, availability, renewability, and low toxicity. Inorganic precursors suitable in the context of the present invention must be soluble or at least partially soluble in the mixture (M1) and must solidify during the gelling process.

[0018] For the purposes of the present invention, a gel is a crosslinked system based on polymers that exists in contact with a liquid (known as a solvogel or lyogel) or with liquid water (aquagel or hydrogel), in which the polymer phase forms a continuous three-dimensional network.

[0019] In the context of the present invention, water soluble means that the solubility in water is sufficient to form a solution that can be used to prepare a gel.

[0020] According to the present invention, a gel is formed from a water-soluble bio-based polyphenol polymer and at least one polyvalent metal ion. In particular, the gel is formed from the components of the mixture (M1) and at least one polyvalent metal ion. The components (C1) and (C2) used in the method of the present invention must be suitable, in particular have suitable functional groups, to allow the formation of a gel with polyvalent metal ions. In particular, the polyphenol polymer used in the method of the present invention must be suitable, in particular have suitable functional groups, to form a gel with polyvalent metal ions.

[0021] Surprisingly, it was found that the claimed method allows the production of aerogels with low solids content, high surface area, preferably high pore volume and small pore size, i.e. aerogels based on water-soluble biobased polyphenol polymers. The properties of the aerogel can be customized by adjusting the composition of the mixture (M1), the reaction conditions in the formation stage of the hydrogel (gel (A)) or the reaction conditions during the solvent exchange and drying stages. According to the invention, it is possible to influence the properties of the hydrogel and / or aerogel not only by changing the ratio of the components but also by controlling the parameters of steps a) and / or b), for example by adjusting the pH value in step a), and also by introducing a wide range of organic and inorganic materials into the gel matrix.

[0022] According to the present invention, the water soluble bio-based polyphenol polymer is preferably selected from the group consisting of lignin biopolymers and tannin biopolymers, in particular alkaline lignin, kraft lignin, hydrolyzed lignin, soda lignin, water soluble solid lignin, enzymatic lignin, lignin sulfonates, lignin carboxylates, lignin derivatives, biorefinery lignin, tannic acid, or tannins and tannin derivatives.

[0023] The mixture (M1) may comprise a further component selected from the group consisting of water-soluble bio-based polyphenol polymers and silica.

[0024] According to a further embodiment, the present invention also relates to the above method, wherein the water soluble biobased polyphenol polymer is selected from lignin biopolymers and tannin biopolymers, in particular alkaline lignin, kraft lignin, hydrolyzed lignin, soda lignin, water soluble solid lignin, enzymatic lignin, lignin sulfonates, lignin carboxylates, lignin derivatives, biorefinery lignin, tannic acid, or tannins and tannin derivatives.

[0025] Compound (C2) may be selected from the group consisting of alginates, pectins, modified celluloses, xanthan, hyaluronic acid or modified starches.According to a further embodiment, the present invention therefore also relates to a method as described above, in which compound (C2) may be selected from the group consisting of alginates, pectins, modified celluloses, xanthan, hyaluronic acid or modified starches, in particular from the group consisting of modified celluloses and alginates, or from the group consisting of alginates.

[0026] According to the invention, the compound (C1) may be selected, for example, from the group consisting of lignin and tannin. It is also possible to use in the mixture (M1) cellulose, bacterial cellulose, modified cellulose, starch, sugars, chitosan, polyhydroxyalkanoates, whey protein isolate, potato protein isolate, starch protein isolate, gelatin, collagen, casein or derivatives thereof, as well as silicates, titanates, vanadates, zirconates, aluminates, borates, ferrates, chromates, molybdates, tungstates, manganates, cobaltates and metal sulfides, oxides and carbides. According to a further embodiment, compound (C1) may be, for example, a mixture comprising lignins and tannins, cellulose, bacterial cellulose, modified cellulose, starch, sugars, chitosan, polyhydroxyalkanoates, whey protein isolate, potato protein isolate, starch protein isolate, gelatin, collagen, casein or derivatives thereof, and a compound selected from the group consisting of silicates, titanates, vanadates, zirconates, aluminates, borates, ferrates, chromates, molybdates, tungstates, manganates, cobaltates and metal sulfides, metal oxides and metal carbides, and compound (C2) may be an alginate or a modified cellulose.

[0027] According to the present invention, the amount of compounds (C1) and (C2) used in the process can vary, for example, depending on the material properties to be achieved. In particular, the amount of bio-based polyphenol polymer used in the process can vary, for example, depending on the material properties to be achieved.

[0028] A suitable amount of compound (C1) is, for example, in the range of 0.1% by mass to 50% by mass based on the mass of mixture (M1), preferably in the range of 0.1% by mass to 40% by mass based on the mass of mixture (M1), in particular in the range of 5.0% by mass to 30% by mass based on the mass of mixture (M1).

[0029] According to a further embodiment, the present invention therefore also relates to the above-mentioned method, wherein mixture (M1) comprises compound (C1) in an amount of 0.1% by weight to 50% by weight, based on the weight of mixture (M1).

[0030] When the mixture (M1) contains the compound (C2), the ratio of the compound (C1) to the compound (C2) may also vary depending on the compound used. Typically, the mixture (M1) contains the compound (C1) to the compound (C2) in a ratio ranging from 55:45 to 98:2, preferably from 60:40 to 95:5.

[0031] According to a further embodiment, the present invention therefore also relates to a method as described above, wherein mixture (M1) comprises compound (C1) and compound (C2) in a ratio ranging from 55:45 to 98:2.

[0032] Additionally, a wide range of organic and inorganic materials can be encapsulated, i.e., physically or co-gelled, into the phenolic polymer matrix, e.g., the lignin matrix, to achieve specific properties, and preferably there are no organic by-products associated with the process.

[0033] In the context of the present invention, the pH value of the mixture (M1) may also vary depending on the compounds used. It has been found that advantageous results are obtained when the pH value of the mixture (M1) is in the range of 8 to 14, in particular in the range of 10 to 14, more preferably in the range of 11 to 14.

[0034] According to a further embodiment, the present invention also relates to the above process, wherein the pH value of the mixture (M1) is in the range of 8-14.

[0035] In the method according to the present invention, according to step a), a mixture (M1) is provided. This mixture can be prepared by dissolving the desired amount of compound (C1) and optionally (C2) in, for example, distilled water. In the context of the present invention, it is also possible to adjust the pH value of the mixture to improve solubility.

[0036] According to step b), the mixture (M1) is contacted with an aqueous solution of polyvalent metal ions to prepare the gel (A).

[0037] The aqueous solution of the polyvalent metal ion can be prepared, for example, using a salt of the polyvalent metal ion.

[0038] According to the invention, polyvalent metal ions that form poorly soluble compounds with the bio-based polyphenol polymer used, especially lignin, i.e. act as bridging metal ions, are preferred. In particular, polyvalent metal ions that can form poorly soluble compounds with the polysaccharide compound (C2) having carboxylic acid groups and can form poorly soluble compounds with the compound (C1) used are preferred. Such polyvalent metal ions include, for example, alkaline earth metal ions and transition metal ions that form poorly soluble compounds with the bio-based polyphenol polymer. Alkaline earth metal ions, such as magnesium or calcium, are preferred. Calcium is particularly preferred. Also trivalent metal ions, such as aluminum or iron (III), are particularly preferred. Calcium salts are particularly preferred according to the invention, since they are physiologically, especially cosmetically acceptable, and have a stronger crosslinking and / or gelling effect compared to lignin. According to the invention, mixtures of two or more polyvalent ions, for example mixtures containing divalent ions and trivalent ions, for example mixtures containing calcium and aluminum or mixtures containing calcium and iron (III), can also be used. Additionally, for example, beryllium, barium, strontium, zinc, cobalt, nickel, copper, manganese, iron, chromium, vanadium, titanium, zirconium, cadmium, molybdenum, tungsten, ruthenium, rhodium, iridium, palladium, platinum, and aluminum may also be used.

[0039] The polyvalent metal ions are preferably added in the form of their salts. In principle, the corresponding anions can be selected as long as they can be solubilized in water as such or by changing the pH. Preferably, chlorides, acetates, nitrates, preferably calcium chloride, or salts of trivalent metals, such as iron(III) chloride, aluminum chloride or iron(III) nitrate, or mixtures thereof, can be used.

[0040] The amount of the salt of the polyvalent metal ion is selected so that the concentration of the salt in the resulting solution is preferably in the range of about 1 to 20 mass%, preferably 1 to 10 mass%, more preferably 1 to 5 mass%, and particularly preferably 2 to 3 mass%.

[0041] According to a further embodiment, the present invention also relates to the above method, wherein the polyvalent metal ion is a divalent metal ion, in particular a divalent metal ion selected from alkaline earth metal ions.

[0042] Mixtures of polyvalent metal ions may also be used in accordance with the present invention.

[0043] The mixture (M1) provided in step (a) may also contain further salts, in particular such salts which do not form gels, and customary auxiliaries known to those skilled in the art as further components.

[0044] Furthermore, the mixture (M1) may contain cosmetic or pharmaceutical active substances.

[0045] According to a further embodiment, the present invention also relates to the above-mentioned method, in which in step a) a compound (C) suitable for forming a gel is added to the mixture (M1). The compound (C) may be soluble or partially soluble in the mixture (M1). In the context of the present invention, it is also possible that the compound (C) is insoluble in the mixture (I).

[0046] According to a further embodiment, the present invention also relates to a method as described above, wherein a compound (C) selected from pigments, opacifiers, flame retardants, metals, metal particles, metal nanoparticles, metal fibers, metal meshes, metal oxides, metal oxide particles, metal oxide nanoparticles, metal oxide fibers, metal salts, catalytic metals, catalytic materials, metal carbide or metal sulfide particles or nanoparticles, silicon-based materials, silicon particles, silicon nanoparticles, semiconductor-based materials, semiconductor particles, semiconductor nanoparticles, semiconductor fibers, semiconductor meshes, carbon materials, carbon black, graphite nanoparticles, graphite fibers, graphite sheets, graphite meshes, graphene nanoparticles, graphene fibers, graphene sheets, graphene meshes, metal-organic frameworks, sulfur, inorganic and / or organic fillers, nucleating agents, stabilizers, thermal control components, surface-active substances, fibers and foam reinforcements is added to the mixture (M1).

[0047] According to a further embodiment, the present invention also relates to the process as described above, wherein a water-insoluble solid (S) is added to the mixture (M1).

[0048] The solid (S) may be, for example, a porous material or foam, a support or a fibrous material. According to the invention, it is also possible for the mixture (M1) to be present in the pores of the solid (S).

[0049] According to step b) of the present invention, the mixture (M1) is contacted with an aqueous solution of polyvalent metal ions to prepare the gel (A). Suitable mixing steps are in principle known to the person skilled in the art. For example, it is possible to add the mixture (M1) dropwise to the aqueous solution of polyvalent metal ions. It is also possible to provide the mixture (M1) in the pores of a support material or in admixture with fibers before contacting it with the aqueous solution of polyvalent metal ions to prepare the gel (A). It is also possible to contact the mixture (M1) with the polyvalent metal ions in an emulsion or in a spray process.

[0050] Gelation is known per se to the person skilled in the art and is described, for example, in WO 2009 / 027310, page 21, line 19 to page 23, line 13.

[0051] Preferably, the temperature and pressure of step b) are adjusted to conditions such that a gel is formed. Suitable temperatures are in the range of 10-40° C., preferably in the range of 15-35° C. According to a further embodiment, the present invention also relates to the above process, wherein step b) is carried out at a temperature in the range of 10-40° C.

[0052] The rate of formation of the insoluble gel can be controlled very accurately and easily by appropriate selection of the conditions of step b).

[0053] The gel (A) obtained in step b) is a gel containing water, i.e. a hydrogel. According to the present invention, in step c) of the method of the present invention, the gel (A) obtained in step b) is exposed to a water-miscible solvent (L) to obtain a gel (B).

[0054] However, it is also possible to use the hydrogel (A) obtained as an intermediate of the above-mentioned process as it is. Many uses of hydrogels are known. The hydrogel (A) is particularly homogeneous and can be used according to the invention to prepare particles, which can be subjected to further processing.

[0055] According to the invention, a water-miscible solvent (L) is used in step c). In the context of the present invention, water-miscible means that the solvent is at least partially miscible with water to allow the exchange of the solvent in the gel.

[0056] Solvent exchange is performed by direct immersion of the gel in a new solvent (single-stage) or by sequential immersion in different water-new solvent mixtures with increasing content of new solvent in the previous immersion stage after a certain time (frequency of exchange) (multi-stage) (Robitzer et al. Langmuir 2008,24,12547-12552). The solvent selected for the replacement of water must meet the following requirements: not dissolve the gel structure, be completely soluble in the previous solvent (water), and be acceptable for pharmaceutical production. Furthermore, if the method includes a step of supercritical drying, the solvent (L) is preferably at least partially miscible with the supercritical medium.

[0057] The solvent (L) can in principle be any suitable compound or mixture of compounds which is liquid under the temperature and pressure conditions of step c) and which fulfills the above requirements.

[0058] Possible solvents (L) include, for example, alcohols, ketones, aldehydes, alkylalkanoates, organic carbonates, amides such as formamide and N-methylpyrrolidone, sulfoxides such as dimethylsulfoxide, aliphatic and cycloaliphatic halogenated or non-halogenated hydrocarbons, halogenated or non-halogenated aromatic compounds, and fluorine-containing ethers. Mixtures of two or more of the abovementioned compounds are likewise possible.

[0059] In many cases, particularly suitable solvents (L) are obtained by using two or more completely miscible compounds selected from the abovementioned solvents.

[0060] Suitable solvents are especially alcohols and ketones, such as C1-C6 alcohols, C1-C6 ketones and mixtures thereof.

[0061] According to a further embodiment, the present invention also relates to the process as described above, wherein the solvent (L) used in step c) is selected from the group consisting of C1-C6 alcohols, C1-C6 ketones and mixtures thereof.

[0062] Alcohols such as methanol, ethanol, isopropanol, and ketones such as acetone, methyl ethyl ketone are particularly suitable.

[0063] The solvent exchange according to step b) can be carried out in one, two, three or multiple steps, with varying solvent concentrations. According to a preferred embodiment, the gel (A) is successively immersed in ethanol / water mixtures having concentrations of, for example, 30, 60, 90 and 100% by weight, respectively, for 5 minutes to 12 hours, depending on the particle size and porosity. For example, it is possible to carry out step b) in two or three steps, using ethanol / water mixtures having ethanol concentrations in the range of more than 60% in the first step and more than 90% in the last step, for example more than 95% or more than 98% in the last step.

[0064] In step c) a gel (B) is obtained. According to step d) of the method of the invention, the gel (B) obtained in step c) is dried.

[0065] The drying in step (d) is carried out in a known manner. Drying under supercritical conditions is preferred, preferably after replacing the solvent with CO2 or another solvent suitable for the purpose of supercritical drying. Such drying is known per se to the person skilled in the art. Supercritical conditions are characterized by temperatures and pressures at which CO2 or the solvent used to remove the gelling solvent is present in the supercritical state. This allows to reduce the shrinkage of the gel body when the solvent is removed.

[0066] In the context of the present invention, it is also possible to dry the gel obtained by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the liquid contained in the gel.

[0067] According to one embodiment, drying of the gel obtained is preferably carried out by converting the solvent (L) into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the solvent (L). Drying is therefore preferably carried out by removing the solvent (L) present during the reaction, without prior replacement with further solvent.

[0068] Such methods are likewise known to the person skilled in the art and are described in WO 2009 / 027310, page 26, line 22 to page 28, line 36.

[0069] According to a further embodiment, the present invention also relates to a method as described above, wherein the drying according to step d) is carried out by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the liquid contained in the gel.

[0070] According to a further embodiment, the present invention also relates to a method as described above, wherein the drying according to step d) is carried out under supercritical conditions.

[0071] The method may also include one or more further modification steps, such as a molding step, a compression step, a lamination step, a post-drying, a hydrophobization step, or a carbonization step, which may include fibers and / or adhesives and / or thermoplastic materials. For example, it is also possible to combine one or more of these steps, such as a post-drying step and a hydrophobization step.

[0072] According to a further embodiment, the present invention also relates to the above method, wherein the method comprises one or more further modification steps of the dried gel.

[0073] According to a further embodiment, the present invention also relates to the above method, wherein the modification step is selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0074] The present invention also relates to a porous material obtained or obtainable by the above process. The porous material of the present invention is preferably an aerogel, a cryogel or a xerogel.

[0075] For purposes of this invention, a xerogel is a porous material produced by a sol-gel process in which the liquid phase is removed from the gel by drying below the critical temperature and pressure of the liquid phase ("subcritical conditions"). A cryogel is a porous material produced by freezing the solvent in the gel and removing the solid solvent by sublimation at ambient temperature. An aerogel is a porous material produced by a sol-gel process in which the liquid phase is removed from the gel under supercritical conditions.

[0076] The above process results in porous materials with improved properties. The aerogels produced according to the process of the invention preferably have a low density and preferably a high specific surface area, e.g., between 120 and 800 m. 2 / g range, or 200-800m 2 / g. More preferably, for pore diameters of less than 150 nm, the specific surface area is in the range of 2.1 to 9.5 cm 3 / g. Furthermore, for pore diameters less than 100 nm, pore volumes in the range of 2.1 to 9.5 cm 3 Pore ​​volumes in the range of 1 / g are preferably obtained.

[0077] Furthermore, the present invention therefore relates to a porous material obtained or obtainable by the method for preparing a porous material as disclosed above. In particular, the present invention relates to a porous material obtained or obtainable by the method for preparing a porous material as disclosed above, in which the drying according to step d) is carried out under supercritical conditions.

[0078] The porous material according to the present invention preferably has a density of 0.005 to 1 g / cm 3 , preferably 0.01 to 0.5 g / cm 3 (determined in accordance with DIN 53420).

[0079] The average pore size is determined by scanning electron microscopy and subsequent image analysis using a statistically significant number of pores. Corresponding methods are known to those skilled in the art. A Nova 3000b Surface Area Analyzer from Quantachrome Instruments was used to characterize the porous structure of the aerogels. It uses nitrogen adsorption and desorption at a constant temperature of 77 K.

[0080] The volume average pore size of the porous material is preferably 1 micron or less. The volume average pore size of the porous material is particularly preferably 750 nm or less, very particularly preferably 500 nm or less, in particular 250 nm or less. The volume average pore size of the porous material can be, for example, in the range of 1 to 1000 nm, preferably in the range of 2 to 500 nm, in particular in the range of 3 to 250 nm, more preferably in the range of 5 to 100 nm, and in particular in the range of 10 to 50 nm.

[0081] The porous material obtainable according to the invention preferably has a porosity of at least 70% by volume, in particular 70-99% by volume, particularly preferably at least 80% by volume, very particularly preferably at least 85% by volume, in particular 85-95% by volume. Porosity in volume % means that a certain percentage of the total volume of the porous material contains pores. From the viewpoint of minimizing thermal conductivity, a very high porosity is usually desirable, but the mechanical properties and processability of the porous material impose an upper limit on the porosity.

[0082] According to a further embodiment, the present invention also relates to a porous material as described above, wherein the specific surface area of ​​the porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 120 and 800 m 2 / g range.

[0083] According to a further embodiment, the present invention also relates to a porous material as described above, wherein the specific surface area of ​​the porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 120 and 800 m 2 / g, and the pore volume is 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 / g range.

[0084] Surprisingly, it has been found according to the invention that it is possible to obtain materials with a very low content of volatile organic compounds, even if the starting materials used contain higher amounts of volatile organic compounds. For example, lignin often contains volatile organic compounds, such as guaiacol, due to its preparation process.

[0085] According to a further embodiment, the present invention therefore also relates to a porous material as described above, wherein the content of volatile organic compounds (VOC) in the porous material is less than 50% of the content of volatile organic compounds (VOC) in the bio-based polyphenol polymer used in the method.

[0086] The porous material obtainable according to the present invention preferably has a high porosity and a low density.Furthermore, the porous material preferably has a small average pore size.The combination of the above-mentioned properties allows this material to be used as an insulating material in the field of thermal insulation, in particular as a building material in ventilated conditions, or for applications in refrigerators, clothing or batteries.

[0087] The present invention also relates to the use of the porous material as described above or of the porous material obtained or obtainable according to the method as described above as an insulation material or for vacuum insulation panels. The insulation material is, for example, an insulation material used for the interior or exterior insulation of buildings. The porous material according to the invention can advantageously be used in insulation systems, for example composite materials.

[0088] Furthermore, the present invention relates to the use of the porous material according to the invention in battery applications, as electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in cosmetic applications, in biomedical applications, in pharmaceutical applications, in agricultural applications and for the manufacture of medical products, such as cosmetic applications including, for example, facial treatment products such as skin scrubs or cleansing, or protective products such as UV protection products or products containing antioxidants.

[0089] According to a further aspect, the present invention relates to a method of use of said porous material or of a porous material obtained or obtainable according to said method as a thermal insulation material, for cosmetic, biomedical or pharmaceutical applications. According to a further preferred aspect, the present invention relates to a method of use of said porous material or of a porous material obtained or obtainable according to said method as a thermal insulation material, as a carrier material for loading and releasing of active agents, for battery applications, as an electrode material in batteries, fuel cells or electrolysis, for catalysis, for capacitors, for home appliances, for building and construction applications, for home and commercial appliance applications, for temperature controlled logistics applications, for vacuum insulation applications, for batteries, for clothing applications, for food applications, for cosmetic applications, for biomedical applications, for agricultural applications, for consumer applications, for packaging applications or for pharmaceutical applications.

[0090] Preferred embodiments are described in the claims and in the specification. Combinations of preferred embodiments do not fall within the scope of the invention. Preferred embodiments of the components used are described below.

[0091] The present invention includes the following embodiments, including certain combinations of the embodiments as indicated by their respective interdependencies defined therein.

[0092] 1. At least the following steps: a) providing a mixture (M1) comprising a water-soluble biobased polyphenol polymer and water; b) contacting the mixture (M1) with an aqueous solution of at least one polyvalent metal ion to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

[0093] 2. The method of embodiment 1, wherein the water soluble bio-based polyphenol polymer is selected from the group consisting of lignin biopolymers and tannin biopolymers, in particular alkaline lignin, kraft lignin, hydrolyzed lignin, soda lignin, water soluble solid lignin, enzymatic lignin, lignin sulfonates, lignin carboxylates, lignin derivatives, biorefinery lignin, tannic acid, or tannins and tannin derivatives.

[0094] 3. The method according to any one of the preceding claims, wherein the mixture (M1) comprises a bio-based polyphenol polymer in an amount ranging from 0.1% to 50% by weight, based on the weight of the mixture (M1).

[0095] 4. The method according to any one of the preceding claims, wherein the pH value of the mixture (M1) is in the range of 8 to 14.

[0096] 5. The method according to any one of the preceding claims, wherein the polyvalent metal ion is a divalent metal ion, in particular a divalent metal ion selected from the group consisting of alkaline earth metal ions, or the polyvalent metal ion is a trivalent metal ion selected from the group consisting of aluminum ions and iron (III) ions.

[0097] 6. The method according to any one of the preceding claims, comprising a further step of modification of the dried gel.

[0098] 7. The method according to embodiment 6, wherein the modification step is selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0099] 8. The method according to any one of the preceding embodiments, wherein the solvent (L) used in step c) is selected from the group consisting of C1-C6 alcohols, C1-C6 ketones and mixtures thereof.

[0100] 9. The method according to any one of the preceding embodiments, wherein a water-insoluble solid (S) is added to the mixture (M1).

[0101] 10. The method according to any one of the preceding claims, wherein a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surface-active substances, thermal control elements, fibers and foam reinforcements is added to the mixture (M1).

[0102] 11. The method according to any one of the preceding claims, wherein the drying according to step d) is carried out by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and pressure of the liquid contained in the gel.

[0103] 12. The method according to any one of the preceding claims, wherein the drying according to step d) is carried out under supercritical conditions.

[0104] 13. A porous material obtained or obtainable by the method according to any one of embodiments 1 to 12.

[0105] 14. The specific surface area of ​​a porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 120 and 800 m 2 / g or 200~800m 2 / g, and the pore volume is 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 14. The porous material of embodiment 13, wherein the porous material has a viscosity in the range of 1 / g.

[0106] 15. The porous material according to embodiment 13 or 14, wherein the content of volatile organic compounds (VOCs) in the porous material is less than 50% of the content of volatile organic compounds (VOCs) in the bio-based polyphenol polymer used in the method.

[0107] 16. Use of the porous material according to any one of embodiments 13 to 15 or obtained or obtainable by the method according to any one of embodiments 1 to 12 as a thermal insulation material, as a carrier material for loading and releasing active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in consumer electronics applications, in temperature controlled logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

[0108] 17. At least the following steps: a) providing a mixture (M1) comprising a water-soluble bio-based (poly)phenolic polymer selected from lignin biopolymers and water; b) contacting the mixture (M1) with an aqueous solution of at least one polyvalent metal ion to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

[0109] 18. The method of embodiment 17, wherein the water soluble bio-based polyphenol polymer is selected from the group consisting of alkaline lignin, kraft lignin, hydrolyzed lignin, soda lignin, water soluble solid lignin, enzymatic lignin, lignin sulfonates, lignin carboxylates, lignin derivatives, and biorefinery lignin.

[0110] 19. The method according to embodiment 17 or 18, wherein the mixture (M1) comprises a bio-based polyphenol polymer in an amount of 0.1% to 50% by weight, based on the weight of the mixture (M1).

[0111] 20. The method according to any one of embodiments 17 to 19, wherein the pH value of the mixture (M1) is in the range of 8 to 14.

[0112] 21. The method according to any one of embodiments 17 to 20, wherein the polyvalent metal ion is a divalent metal ion, in particular a divalent metal ion selected from the group consisting of alkaline earth metal ions, or the polyvalent metal ion is a trivalent metal ion selected from the group consisting of aluminum ions and iron (III) ions.

[0113] 22. The method according to any one of embodiments 17 to 21, comprising a further modification step of the dried gel.

[0114] 23. The method of embodiment 22, wherein the modification step is selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0115] 24. The method according to any one of embodiments 17 to 23, wherein the solvent (L) used in step c) is selected from the group consisting of C1 to C6 alcohols, C1 to C6 ketones, and mixtures thereof.

[0116] 25. The method according to any one of embodiments 17 to 24, wherein a water-insoluble solid (S) is added to the mixture (M1).

[0117] 26. The method according to any one of embodiments 17 to 25, wherein a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surfactants, thermal control elements, fibers and foam reinforcements is added to the mixture (M1).

[0118] 27. The method according to any one of embodiments 17 to 26, wherein the drying according to step d) is carried out by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the liquid contained in the gel.

[0119] 28. The method according to any one of embodiments 17 to 26, wherein the drying according to step d) is carried out under supercritical conditions.

[0120] 29. A porous material obtained or obtainable by the method according to any one of embodiments 17 to 28.

[0121] 30. The specific surface area of ​​a porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 120 and 800 m 2 / g or 200~800m 2 / g, and the pore volume is 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 30. The porous material of embodiment 29, wherein the porous material has a viscosity in the range of 1 / g.

[0122] 31. The porous material of embodiment 29 or 30, wherein the content of volatile organic compounds (VOCs) in the porous material is less than 50% of the content of volatile organic compounds (VOCs) in the bio-based polyphenol polymer used in the method.

[0123] 32. Use of the porous material according to any one of embodiments 29 to 31 or obtained or obtainable by the method according to any one of embodiments 17 to 28 as a thermal insulation material, as a carrier material for loading and releasing active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in consumer electronics applications, in temperature controlled logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

[0124] 33. At least the following steps: a) providing a mixture (M1) comprising a water-soluble bio-based (poly)phenolic polymer selected from the group consisting of lignin biopolymers, and water; b) contacting the mixture (M1) with an aqueous solution of at least one polyvalent metal ion to prepare a gel (A), said polyvalent metal ion being a divalent metal ion; c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

[0125] 34. The method of embodiment 33, wherein the water soluble bio-based polyphenol polymer is selected from the group consisting of alkaline lignin, kraft lignin, hydrolyzed lignin, soda lignin, water soluble solid lignin, enzymatic lignin, lignin sulfonates, lignin carboxylates, lignin derivatives, and biorefinery lignin.

[0126] 35. The method according to embodiment 33 or 34, wherein the mixture (M1) comprises a bio-based polyphenol polymer in an amount of 0.1% to 50% by weight, based on the weight of the mixture (M1).

[0127] 36. The method according to any one of embodiments 33 to 35, wherein the pH value of the mixture (M1) is in the range of 8 to 14.

[0128] 37. The method of any one of embodiments 33 to 36, wherein the polyvalent metal ion is a divalent metal ion selected from the group consisting of alkaline earth metal ions, or the polyvalent metal ion is a trivalent metal ion selected from the group consisting of aluminum ions and iron (III) ions.

[0129] 38. The method according to any one of embodiments 33 to 37, comprising a further modification step of the dried gel.

[0130] 39. The method of embodiment 38, wherein the modification step is selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0131] 40. The method according to any one of embodiments 33 to 39, wherein the solvent (L) used in step c) is selected from the group consisting of C1 to C6 alcohols, C1 to C6 ketones, and mixtures thereof.

[0132] 41. The method according to any one of embodiments 33 to 40, wherein a water-insoluble solid (S) is added to the mixture (M1).

[0133] 42. The method according to any one of embodiments 33 to 41, wherein a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surface-active substances, thermal control components, fibers and foam reinforcements is added to the mixture (M1).

[0134] 43. The method according to any one of embodiments 33 to 42, wherein the drying according to step d) is carried out by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the liquid contained in the gel.

[0135] 44. The method according to any one of embodiments 33 to 42, wherein the drying according to step d) is carried out under supercritical conditions.

[0136] 45. A porous material obtained or obtainable by the method according to any one of embodiments 33 to 44.

[0137] 46. ​​The specific surface area of ​​a porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 120 and 800 m 2 / g or 200~800m 2 / g, and the pore volume is 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 46. ​​The porous material of embodiment 45, wherein the porous material has a viscosity in the range of 1 / g.

[0138] 47. The porous material of embodiment 45 or 46, wherein the content of volatile organic compounds (VOCs) in the porous material is less than 50% of the content of volatile organic compounds (VOCs) in the bio-based polyphenol polymer used in the method.

[0139] 48. Use of the porous material according to any one of embodiments 45 to 47 or the porous material obtained or obtainable by the method according to any one of embodiments 33 to 44 as a thermal insulation material, as a carrier material for loading and releasing active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in consumer electronics applications, in temperature controlled logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

[0140] 49. At least the following steps: a) providing a mixture (M1) comprising a water-soluble bio-based polyphenol polymer selected from the group consisting of lignin biopolymers and tannin biopolymers, and water; b) contacting the mixture (M1) with an aqueous solution of at least one divalent metal ion to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

[0141] 50. At least the following steps: a) providing a mixture (M1) comprising a water-soluble bio-based polyphenol polymer selected from the group consisting of lignin biopolymers and tannin biopolymers, and water; b) contacting the mixture (M1) with an aqueous solution of at least one divalent metal ion to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising: The method, wherein the mixture (M1) further comprises, as compound (C2), at least one water-soluble polysaccharide having a carboxylic acid group.

[0142] 51. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of water-soluble bio-based polymers and inorganic precursors, at least one water-soluble polysaccharide having carboxylic acid groups as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

[0143] 52. The method according to embodiment 51, wherein compound (C1) is selected from the group consisting of water-soluble bio-based polyphenol polymers and silica.

[0144] 53. The method according to embodiment 51 or 52, wherein mixture (M1) comprises compound (C1) in an amount of 0.1% to 50% by weight, based on the weight of mixture (M1).

[0145] 54. The method according to any one of embodiments 51 to 53, wherein mixture (M1) comprises compound (C1) and compound (C2) in a ratio ranging from 55:45 to 98:2.

[0146] 55. The method according to any one of embodiments 51 to 54, wherein the pH value of the mixture (M1) is in the range of 8 to 14.

[0147] 56. The method according to any one of embodiments 51 to 55, wherein the polyvalent metal ion is a divalent metal ion, in particular a divalent metal ion selected from the group consisting of alkaline earth metal ions, or the polyvalent metal ion is a trivalent metal ion selected from the group consisting of aluminum ions and iron (III) ions.

[0148] 57. The method according to any one of embodiments 51 to 56, wherein the method comprises one or more further modification steps of the dried gel, in particular the modification steps being selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0149] 58. The method according to any one of embodiments 51 to 57, wherein the solvent (L) used in step c) is selected from the group consisting of C1 to C6 alcohols, C1 to C6 ketones, and mixtures thereof.

[0150] 59. The method according to any one of embodiments 51 to 58, wherein a water-insoluble solid (S) is contacted with the mixture (M1).

[0151] 60. The method according to any one of embodiments 51 to 59, wherein a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surface-active substances, thermal control components, fibers and foam reinforcements is added to the mixture (M1).

[0152] 61. The method according to any one of embodiments 51 to 60, wherein the drying according to step d) is carried out by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the liquid contained in the gel.

[0153] 62. The method according to any one of embodiments 51 to 60, wherein the drying according to step d) is carried out under supercritical conditions.

[0154] 63. A porous material obtained or obtainable by the method according to any one of embodiments 51 to 62.

[0155] 64. The specific surface area of ​​a porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 120 and 800 m 2 / g or 200~800m 2 / g, and the pore volume is 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 64. The porous material of embodiment 63, wherein the porous material has a viscosity in the range of 1 / g.

[0156] 65. The porous material of embodiment 63 or 64, wherein the content of volatile organic compounds (VOCs) in the porous material is less than 50% of the content of volatile organic compounds (VOCs) in the starting material used in the method.

[0157] 66. Use of the porous material according to any one of embodiments 63 to 65 or the porous material obtained or obtainable by the method according to any one of embodiments 51 to 62 as a thermal insulation material, as a carrier material for loading and releasing active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in consumer electronics applications, in temperature controlled logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

[0158] 67. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of water-soluble bio-based polymers and silica, at least one water-soluble polysaccharide having carboxylic acid groups as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

[0159] 68. The method according to embodiment 67, wherein compound (C1) is selected from the group consisting of lignin biopolymers and silica.

[0160] 69. The method according to embodiment 67 or 68, wherein mixture (M1) comprises compound (C1) in an amount of 0.1% to 50% by weight, based on the weight of mixture (M1).

[0161] 70. The method according to any one of embodiments 67 to 69, wherein mixture (M1) comprises compound (C1) and compound (C2) in a ratio ranging from 55:45 to 98:2.

[0162] 71. The method according to any one of embodiments 67 to 70, wherein the pH value of the mixture (M1) is in the range of 8 to 14.

[0163] 72. The method according to any one of embodiments 67 to 71, wherein the polyvalent metal ion is a divalent metal ion, in particular a divalent metal ion selected from the group consisting of alkaline earth metal ions, or the polyvalent metal ion is a trivalent metal ion selected from the group consisting of aluminum ions and iron (III) ions.

[0164] 73. The method according to any one of embodiments 67 to 72, wherein the method comprises one or more further modification steps of the dried gel, in particular the modification steps being selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0165] 74. The method according to any one of embodiments 67 to 73, wherein the solvent (L) used in step c) is selected from the group consisting of C1 to C6 alcohols, C1 to C6 ketones, and mixtures thereof.

[0166] 75. The method according to any one of embodiments 67 to 74, wherein a water-insoluble solid (S) is contacted with the mixture (M1).

[0167] 76. The method according to any one of embodiments 67 to 75, wherein a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surface-active substances, thermal control components, fibers and foam reinforcements is added to the mixture (M1).

[0168] 77. The method according to any one of embodiments 27 to 76, wherein the drying according to step d) is carried out by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the liquid contained in the gel.

[0169] 78. The method according to any one of embodiments 27 to 76, wherein the drying according to step d) is carried out under supercritical conditions.

[0170] 79. A porous material obtained or obtainable by the method according to any one of embodiments 27 to 78.

[0171] 80. The specific surface area of ​​a porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 120 and 800 m 2 / g or 200~800m 2 / g, and the pore volume is 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 80. The porous material of embodiment 79, wherein the porous material has a viscosity in the range of 1 / g.

[0172] 81. The porous material of embodiment 79 or 80, wherein the content of volatile organic compounds (VOCs) in the porous material is less than 50% of the content of volatile organic compounds (VOCs) in the starting material used in the method.

[0173] 82. Use of the porous material according to any one of embodiments 79 to 81 or the porous material obtained or obtainable by the method according to any one of embodiments 67 to 78 as a thermal insulation material, as a carrier material for loading and releasing active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in consumer electronics applications, in temperature controlled logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

[0174] 83. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of water-soluble lignin biopolymers and silica, at least one water-soluble polysaccharide having carboxylic acid groups as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising: The method, wherein the compound (C2) is selected from the group consisting of alginates, pectins, modified celluloses, xanthan, hyaluronic acid or modified starches.

[0175] 84. The method according to embodiment 83, wherein the compound (C2) is selected from the group consisting of alginates.

[0176] 85. The method according to embodiment 83 or 84, wherein mixture (M1) comprises compound (C1) in an amount of 0.1% to 50% by weight, based on the weight of mixture (M1).

[0177] 86. The method according to any one of embodiments 83 to 85, wherein mixture (M1) comprises compound (C1) and compound (C2) in a ratio ranging from 55:45 to 98:2.

[0178] 87. The method according to any one of embodiments 83 to 86, wherein the pH value of the mixture (M1) is in the range of 8 to 14.

[0179] 88. The method according to any one of embodiments 83 to 87, wherein the polyvalent metal ion is a divalent metal ion, in particular a divalent metal ion selected from the group consisting of alkaline earth metal ions, or the polyvalent metal ion is a trivalent metal ion selected from the group consisting of aluminum ions and iron (III) ions.

[0180] 89. The method according to any one of embodiments 83 to 88, wherein the method comprises one or more further modification steps of the dried gel, in particular the modification steps being selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

[0181] 90. The method according to any one of embodiments 83 to 89, wherein the solvent (L) used in step c) is selected from the group consisting of C1 to C6 alcohols, C1 to C6 ketones, and mixtures thereof.

[0182] 91. The method according to any one of embodiments 83 to 90, wherein a water-insoluble solid (S) is contacted with the mixture (M1).

[0183] 92. The method according to any one of embodiments 83 to 91, wherein a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surface-active substances, thermal control components, fibers and foam reinforcements is added to the mixture (M1).

[0184] 93. The method according to any one of embodiments 83 to 92, wherein the drying according to step d) is carried out by converting the liquid contained in the gel into the gaseous state at a temperature and pressure below the critical temperature and critical pressure of the liquid contained in the gel.

[0185] 94. The method according to any one of embodiments 83 to 92, wherein the drying according to step d) is carried out under supercritical conditions.

[0186] 95. A porous material obtained or obtainable by the method according to any one of embodiments 83 to 94.

[0187] 96. The specific surface area of ​​a porous material is determined using the BET theory according to DIN 66134:1998-0 and is between 120 and 800 m 2 / g or 200~800m 2 / g, and the pore volume is 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 96. The porous material of embodiment 95, wherein the porous material has a viscosity in the range of 1:1 / g.

[0188] 97. The porous material of embodiment 95 or 96, wherein the content of volatile organic compounds (VOCs) in the porous material is less than 50% of the content of volatile organic compounds (VOCs) in the starting material used in the method.

[0189] 98. Use of the porous material according to any one of embodiments 95 to 97 or the porous material obtained or obtainable by the method according to any one of embodiments 83 to 94 as a thermal insulation material, as a carrier material for loading and releasing active agents, in battery applications, as an electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in consumer electronics applications, in temperature controlled logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

[0190] 83. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of water-soluble lignin biopolymer silica, at least one water-soluble polysaccharide having carboxylic acid groups as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of polyvalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising: The method, wherein the compound (C2) is selected from the group consisting of alginates, pectins, modified celluloses, xanthan, hyaluronic acid or modified starches.

[0191] 99. At least the following steps: a) providing a mixture (M1) comprising at least one compound (C1) selected from the group consisting of lignin biopolymers and silica, at least one water-soluble polysaccharide having carboxylic acid groups as component (C2), and water; b) contacting the mixture (M1) with an aqueous solution of divalent or trivalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising: The method, wherein the compound (C2) is selected from the group consisting of alginates, pectins, modified celluloses, xanthan, hyaluronic acid or modified starches.

[0192] 100. At least the following steps: a) providing a mixture (M1) comprising water, at least one compound (C1) selected from the group consisting of lignin biopolymers and silica, and at least one component (C2) selected from the group consisting of alginates; b) contacting the mixture (M1) with an aqueous solution of divalent or trivalent metal ions to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

[0193] The present invention will now be described with reference to examples. EXAMPLES

[0194] 1. Materials Used Ingredients: Kraft lignin (UPM), Sodium hydroxide (NaOH, Sigma Aldrich), Calcium chloride (CaCl2, Sigma Aldrich), Pure ethanol (Carl Roth), Sodium alginate (Hydagen, BASF), Hexamethyldisilazane (HMDZ, Sigma Aldrich), Ludox SM30 (Sigma Aldrich), Whey protein (Agropure Ingredients), Xanthan (Sigma Aldrich), Microcrystalline cellulose (MCC, Sigma Aldrich), Sodium caseinate (Sigma Aldrich), Tannic acid (Sigma Aldrich), Potato starch (Sigma Aldrich), Gelatin (Sigma Aldrich).

[0195] 2. Preparation Example 2.1 Hydrophilic lignin aerogel from kraft lignin - Ca gelation Solution 1: Kraft lignin powder (~6000 g / mol, UPM) was dispersed in deionized water (20 wt%) at room temperature and 5 wt% NaOH was added until the pH was 11.5. After 1 day, the pH was measured and an additional 5 wt% NaOH was added until the pH was 11.5.

[0196] Solution 2: A CaCl2 aqueous solution (20 g / L) was prepared at room temperature.

[0197] Solution 1 was added dropwise to solution 2 (10 times the volume) with a pipette. Small hydrogel particles formed and settled to the bottom of solution 2.

[0198] The hydrogel particles were filtered through a 125 μm sieve.

[0199] The hydrogel particles were immersed in ethanol (93%) for 5 min. A final solvent exchange step was performed by immersing the hydrogel particles from the previous step in pure ethanol for 5 min to obtain alcogel particles (final solvent concentration 94–98%).

[0200] The alcogel particles were dried with supercritical carbon dioxide at 60 °C and 120 bar for 1 h to obtain lignin aerogel particles, which do not have the odor of the original kraft lignin feedstock.

[0201] Surface area: 297m 2 / g Pore ​​volume: 2.4cm 3 / g BJH pore size: 12nm Aerogel density: 200~300g / l Contact angle: 0°.

[0202] 2.2 Hydrophilic lignin aerogel from kraft lignin - Zn gelation Solution 1: Kraft lignin powder (~6000 g / mol, UPM) was dispersed (10% by weight) in deionized water at room temperature and 5% by weight NaOH was added until the pH was 11. After 1 day, the pH was measured and an additional 5% by weight NaOH was added until the pH was 11.

[0203] Solution 2: A ZnCl2 aqueous solution (10 g / L) was prepared at room temperature.

[0204] Solution 1 was added dropwise to solution 2 (10 times the volume) with a pipette. Small hydrogel particles formed and settled to the bottom of solution 2.

[0205] The hydrogel particles were immersed in ethanol (93%, 10x volume) for 5 min. A final solvent exchange step was performed by immersing the gel particles from the previous step in pure ethanol (10x volume) for 5 min to obtain alcogel particles (final solvent concentration 94–98%).

[0206] The alcogel particles were dried using supercritical carbon dioxide at 60 °C and 120 bar for 1 h to obtain lignin aerogel particles.

[0207] The bulk density of the lignin aerogel particles 5 was 80 to 120 g / l.

[0208] The measured surface area and pore volume of the lignin aerogel particles were 308 m 2 / g.

[0209] 2.3 Hydrophilic lignin aerogel from kraft lignin - Sr gelation Solution 1: Kraft lignin powder (~6000 g / mol, UPM) was dispersed (20% by weight) in deionized water at room temperature and 5% by weight NaOH was added until the pH was 11. After 1 day, the pH was measured and an additional 5% by weight NaOH was added until the pH was 10.5.

[0210] Solution 2: An aqueous solution of SrCl2 (10 g / L) was prepared at room temperature (pH 7.8).

[0211] Solution 1 was added dropwise to solution 2 (10 times the volume) with a pipette. Small hydrogel particles formed and settled to the bottom of solution 2.

[0212] The hydrogel particles were immersed in ethanol (93%, 10x volume) for 5 min. A final solvent exchange step was performed by immersing the gel particles from the previous step in pure ethanol (10x volume) for 5 min to obtain alcogel particles (final solvent concentration 94–98%).

[0213] The alcogel particles were dried using supercritical carbon dioxide at 60 °C and 120 bar for 1 h to obtain lignin aerogel particles.

[0214] The bulk density of the aerogel particles 5 was 160 to 200 g / l.

[0215] The measured surface area of ​​the aerogel particles is 273 m 2 / g.

[0216] 2.4 Hydrophilic lignin aerogel from biorefinery lignin Solution 1: Biorefinery lignin powder was dispersed in deionized water at room temperature (20% by weight) and 5% by weight NaOH was added until the pH was 10.4. After 1 day, the pH was measured and an additional 5% by weight NaOH was added until the pH was 10.5.

[0217] Solution 2: A CaCl2 aqueous solution (10 g / L) was prepared at room temperature.

[0218] Solution 1 was added dropwise to solution 2 (10 times the volume) with a pipette. Hydrogel particles formed and settled to the bottom of solution 2.

[0219] The hydrogel particles were immersed in ethanol (93%, 10x volume) for 5 min. A final solvent exchange step was performed by immersing the gel particles from the previous step in pure ethanol (10x volume) for 5 min to obtain alcogel particles (final solvent concentration 94–98%).

[0220] The alcogel particles were dried using supercritical carbon dioxide at 60 °C and 120 bar for 1 h to obtain lignin aerogel particles.

[0221] The measured surface area of ​​the aerogel particles is 151 m 2 / g.

[0222] 3. Preparation example - hybrid material 3.1 Hydrophilic kraft lignin / alginate hybrid aerogel Solution 1: Kraft lignin powder was dispersed in deionized water at room temperature (14% by weight) and 5% by weight NaOH was added until the pH was 10. Sodium alginate was added and dissolved to obtain a kraft lignin to alginate mass ratio of 92:8.

[0223] Solution 2: An aqueous CaCl2 solution (10 g / L) was prepared at room temperature and adjusted to a pH of 10 with 1 M NaOH.

[0224] Solution 1 was added dropwise to solution 2 (10 times the volume) with a pipette. Hydrogel particles formed and settled to the bottom of solution 2.

[0225] The hydrogel particles were immersed in ethanol (93%, 10x volume) for 5 min. A final solvent exchange step was performed by immersing the gel particles from the previous step in pure ethanol (10x volume) for 5 min to obtain alcogel particles (final solvent concentration 94–98%).

[0226] The alcogel particles were dried using supercritical carbon dioxide at 60 °C and 120 bar for 1 h to obtain kraft lignin / alginate hybrid aerogel particles.

[0227] The bulk density of the aerogel particles 5 was ∼120 g / l.

[0228] The measured surface area of ​​the aerogel particles is 255 m 2 / g and the pore volume is 1.88 cm 3 / g.

[0229] 3.2 Hydrophilic Kraft Lignin / Alginate Hybrid Aerogels – Various Ratios Solution 1: Kraft lignin powder was dispersed in deionized water (10% by weight) at room temperature and 5% by weight NaOH was added until the pH was 11. After 1 day, the pH was measured and an additional 5% by weight NaOH was added until the pH was 11.

[0230] Solution 2: Sodium alginate was dissolved in water (2% by weight) at room temperature.

[0231] Solution 3: A CaCl2 aqueous solution (20 g / L) was prepared at room temperature.

[0232] Solutions 1 and 2 were combined in various mass ratios and the total concentration of kraft lignin and alginic acid was adjusted by adding water to obtain solutions 4a–e: Solution 4a: Kraft lignin / alginic acid 1:2 (2.7% by weight, pH = 10.2) Solution 4b: Kraft lignin / alginic acid 1:1 (2.7% by weight, pH = 10.6) Solution 4c: Kraft lignin / alginic acid 2:1 (2.7% by weight, pH = 10.7) Solution 4d: Kraft lignin / alginic acid 4:1 (2.7% by weight, pH = 10.7) Solution 4e: Kraft lignin / alginic acid 9:1 (2.7% by weight, pH = 10.7).

[0233] 50 ml of solutions 4a-e were dropped into solution 3 (10 times the volume) with a pipette. Hydrogel particles 5a-e based on 4a-e were formed and precipitated to the bottom of solution 3.

[0234] Hydrogel particles 5a–e were immersed in ethanol (93%, 10x volume) for 5 min. A final solvent exchange step was performed by immersing gel particles 5a–e from the previous step in pure ethanol (10x volume) for 5 min to obtain alcogel particles 6a–e (final solvent concentration 94–98%).

[0235] The alcogel particles 6a–e were dried for 1 h at 60 °C and 120 bar using supercritical carbon dioxide to obtain kraft lignin / alginate hybrid aerogel particles 7a–e. The aerogel particles 7a–e do not have the odor of kraft lignin. The aerogel particles 7a–e were used directly for hydrophobization.

[0236] 3.3 Hydrophobic kraft lignin / alginate hybrid aerogels – various ratios 50 ml of hydrophilic lignin aerogel particles 7a-e obtained in the previous example 3.2 were placed in a filter bag and placed in a 2 liter reactor. 50 ml of HMDZ was also placed in a small open container and placed in the reactor. The reactor was closed and heated to 115 °C. After 20 hours, the reactor was cooled to room temperature and the hydrophobic aerogel particles 8a-e were removed from the reactor.

[0237] The densities of the aerogel particles 8a-e were in the range of 45 g / l.

[0238] The surface area of ​​aerogel particles 8a-e was measured (as described above). Hydrophobicity was tested by placing aerogel particles 8a-e on water in a container and observing the color change (color changes from light brown to dark brown upon taking up water) and shrinkage.

[0239] 8a: Surface area is 429 m 2 / g. When placed on water, the aerogel particles immediately changed from light brown to dark brown (uptake of water) and contracted by ~50% within ~10 seconds.

[0240] 8b: Surface area is 394 m 2 / g. When placed on water, the aerogel particles immediately changed from light brown to dark brown and shrunk by ~50% within ~30 seconds.

[0241] 8c: Surface area 372m 2 / g. When placed on water, the aerogel particles contracted by ~50% within ~10 minutes, and the color of the particles changed from light brown to dark brown (water uptake) over the course of an hour.

[0242] 8d: Surface area 330m 2 / g. When placed on water, the aerogel particles contracted by ~50% within ~2 hours, and the color of the particles changed from light brown to dark brown (water uptake) over 4 hours.

[0243] 8e: Surface area 318m 2 / g. When placed on water, the aerogel particles shrunk by ~50% within ~4 hours, and the color of the particles changed from light brown to dark brown (water uptake) over 8 hours.

[0244] 3.4 Hydrophilic lignin sulfonate / xanthan hybrid aerogel Solution 1: Ligninsulfonate powder was dispersed in deionized water at room temperature (40% by weight) and 5% by weight of NaOH was added until a pH of 13 was reached.

[0245] Solution 2: Xanthan was dispersed in an equal amount of ethanol and then dissolved to 0.7% by weight in water at room temperature.

[0246] Solution 3: A CaCl2 aqueous solution (10 g / L) was prepared at room temperature.

[0247] Solutions 1 and 2 were combined in a lignin sulfonate to xanthan mass ratio of 95:5 to obtain solution 4.

[0248] Solution 4 was added dropwise to solution 3 (10 times the volume) with a pipette. Hydrogel particles formed and settled to the bottom of solution 3.

[0249] The hydrogel particles were immersed in ethanol (93%, 10x volume) for 5 min. A final solvent exchange step was performed by immersing the gel particles from the previous step in pure ethanol (10x volume) for 5 min to obtain alcogel particles (final solvent concentration 94–98%).

[0250] The alcogel particles were dried using supercritical carbon dioxide at 60 °C and 120 bar for 1 h to obtain lignin sulfonate / xanthan hybrid aerogel particles.

[0251] The density of the aerogel particles was ~200 g / l.

[0252] The measured surface area of ​​the aerogel particles is 290 m 2 / g.

[0253] 3.5 Hydrophilic kraft lignin / xanthan hybrid aerogel Solution 1: Kraft lignin powder was dispersed in deionized water at room temperature (20 wt%) and 5 wt% NaOH was added until the pH was 13.5.

[0254] Solution 2: Xanthan was dispersed in an equal amount of ethanol and then dissolved to 0.7% by weight in water at room temperature.

[0255] Solution 3: A CaCl2 aqueous solution (10 g / L) was prepared at room temperature.

[0256] Solutions 1 and 2 were combined in a kraft lignin to xanthan mass ratio of 97:3 to obtain solution 4.

[0257] Solution 4 was added dropwise to solution 3 (10 times the volume) with a pipette. Hydrogel particles formed and settled to the bottom of solution 3.

[0258] The hydrogel particles were immersed in ethanol (93%, 10x volume) for 5 min. A final solvent exchange step was performed by immersing the gel particles from the previous step in pure ethanol (10x volume) for 5 min to obtain alcogel particles (final solvent concentration 94–98%).

[0259] The alcogel particles were dried using supercritical carbon dioxide at 60 °C and 120 bar for 1 h to obtain kraft lignin / xanthan hybrid aerogel particles.

[0260] The density of the aerogel particles was ~200 g / l.

[0261] The measured surface area of ​​the aerogel particles is 416 m 2 / g.

[0262] 3.6 Hybrid aerogels with three or more components Solution 1: Kraft lignin powder was dispersed in deionized water at room temperature (14% by weight) and 5% by weight of NaOH was added until the pH reached 10. Ludox SM30 (colloidal silica) was added and sodium alginate was added and dissolved in various proportions and the concentration was adjusted with water to obtain the various solutions 1 shown in Table 1.

[0263] Solution 2: An aqueous CaCl2 solution (10 g / L) was prepared at room temperature and adjusted to a pH of 10 with 1 M NaOH.

[0264] Solution 1 was added dropwise to solution 2 (10 times the volume) with a pipette. Hydrogel particles formed and settled to the bottom of solution 2.

[0265] The hydrogel particles were immersed in ethanol (93%, 10x volume) for 5 min. A final solvent exchange step was performed by immersing the gel particles from the previous step in pure ethanol (10x volume) for 5 min to obtain alcogel particles (final solvent concentration 94–98%).

[0266] The alcogel particles were dried using supercritical carbon dioxide at 60 °C and 120 bar for 1 h to obtain the colloidal silica / kraft lignin / alginate hybrid aerogel particles shown in Table 1.

[0267] [Table 1]

[0268] 3.7 Hybrid aerogels with various biopolymers Solution 1: Tannic acid was mixed with 2% by weight sodium alginate solution to obtain various solutions with the concentrations and weight ratios shown in Table 2. 40% by weight NaOH was added to the various solutions until the pH shown in Table 2 was obtained.

[0269] Solution 2: An aqueous CaCl2 solution (10 g / L) was prepared at room temperature and adjusted to a pH of 10 with 1 M NaOH.

[0270] Solution 1 was added dropwise to solution 2 (10 times the volume) with a pipette. Hydrogel particles formed and settled to the bottom of solution 2.

[0271] The hydrogel particles were immersed in ethanol (93%, 10x volume) for 5 min. A final solvent exchange step was performed by immersing the gel particles from the previous step in pure ethanol (10x volume) for 5 min to obtain alcogel particles (final solvent concentration 94–98%).

[0272] The alcogel particles were dried using supercritical carbon dioxide at 60° C. and 120 bar for 1 hour to obtain hydrophilic hybrid aerogel particles with the concentrations and mass ratios shown in Table 2.

[0273] For hydrophobization, 50 ml of hydrophilic aerogel particles were placed in a filter bag and placed in a 2 liter reactor. 50 ml of HMDZ was also placed in a small open container and placed in the reactor. The reactor was closed and heated to 115°C. After 20 hours, the reactor was cooled to room temperature and hydrophobic aerogel particles with the surface areas shown in Table 2 were removed from the reactor.

[0274] [Table 2]

[0275] 4. Methods Used 4.1 Pore volume The pore volume was measured using a Nova 4000e pore size analyzer from Quantachrome Instruments according to DIN 66134:1998-02. Approximately 15-20 mg of sample was divided from the original sample and placed in a measuring glass cell. The sample was degassed at 60°C under a vacuum of 50 mm Hg for 15 hours to remove any adsorbed components on the sample. The mass of the sample was measured again before analyzing the surface area and pore size.

[0276] 4.2 Surface area measurements: The specific surface area was measured by the Brunauer-Emmet-Teller (BET) method using low-temperature nitrogen adsorption analysis (at the boiling point of nitrogen, 77 K) in the P / P0 range recommended by IUPAC (0.05-0.30). A graph of 1 / ((w.(P0 / P-1))) versus P / P0 gave a linear plot with a correlation coefficient (r) of more than 0.999.

[0277] References: US020190329208A1 Grishechko, L. et al., Industrial Crops and Products, 2013, 41, 347~355 WO 2009 / 027310 Robitzer et al., Langmuir, 2008, 24, 12547-12552 WO 2009 / 027310

Claims

1. At least the following steps: a) providing a mixture (M1) comprising a water-soluble bio-based polyphenol polymer selected from the group consisting of lignin biopolymers and tannin biopolymers as compound (C1), and water; b) contacting the mixture (M1) with an aqueous solution of at least one polyvalent metal ion to prepare a gel (A); c) exposing the gel (A) obtained in step b) to a water-miscible solvent (L) to obtain a gel (B); d) drying the gel (B) obtained in step c); A method for preparing a porous material comprising:

2. 2. The method according to claim 1, wherein the mixture (M1) further comprises, as compound (C2), at least one water-soluble polysaccharide having a carboxylic acid group.

3. 3. The method of claim 1 or 2, wherein the water soluble bio-based polyphenol polymer is selected from the group consisting of alkaline lignin, kraft lignin, hydrolyzed lignin, soda lignin, water soluble solid lignin, enzymatic lignin, lignin sulfonates, lignin carboxylates, lignin derivatives, biorefinery lignin, tannic acid, or tannins and tannin derivatives.

4. 3. The method according to claim 1 or 2, wherein the mixture (M1) comprises a bio-based polyphenol polymer in an amount of 0.1% to 50% by weight, based on the weight of the mixture (M1).

5. The method according to claim 1 or 2, wherein the mixture (M1) comprises the compound (C1) and the compound (C2) in a ratio ranging from 55:45 to 98:

2.

6. 3. The method according to claim 1 or 2, wherein the pH value of the mixture (M1) is in the range of 8 to 14.

7. 3. The method according to claim 1 or 2, wherein the polyvalent metal ion is a divalent or trivalent metal ion, preferably a divalent or trivalent metal ion selected from the group consisting of alkaline earth metal ions, aluminium ions and iron (III) ions.

8. 3. The method of claim 1 or 2, comprising one or more further modification steps of the dried gel.

9. The method of claim 8, wherein the modification step is selected from the group consisting of a molding step, a compression step, a lamination step, a post-drying step, a hydrophobization step, and a carbonization step.

10. 3. The process according to claim 1 or 2, wherein the solvent (L) used in step c) is selected from the group consisting of C1-C6 alcohols, C1-C6 ketones and mixtures thereof.

11. - water-insoluble solids (S), and / or a compound (C) selected from the group consisting of pigments, opacifiers, flame retardants, catalytic materials, metals, metal oxides, metal sulfides, metal carbides, metal salts, silicon-based materials, carbon-based materials, metal-organic frameworks, semiconductors, sulfur, fillers, surface-active substances, thermal control components, fibers and foam reinforcements, 3. The method according to claim 1 or 2, wherein the mixture (M1) is added.

12. 2. A porous material obtained or obtainable by the method of claim 1.

13. The specific surface area of ​​the porous material is determined using the BET theory in accordance with DIN 66134:1998-0 and is in the range of 120 to 800 m 2 / g and the pore volume is in the range of 2.1 to 9.5 cm for pore diameters less than 150 nm. 3 The porous material according to claim 12, wherein the molecular weight is in the range of 1 / g.

14. 14. The porous material according to claim 12 or 13, wherein the content of volatile organic compounds (VOC) in the porous material is less than 50% of the content of volatile organic compounds (VOC) in the starting material used in the method.

15. 13. Use of the porous material according to claim 12 or obtained or obtainable by the method according to claim 1 as a thermal insulation material, as a carrier material for loading and releasing of active agents, in battery applications, electrode material in batteries, fuel cells or electrolysis, in catalysis, in capacitors, in home appliances, in building and construction applications, in consumer electronics applications, in temperature controlled logistics applications, in vacuum insulation applications, in clothing applications, in food applications, in cosmetic applications, in biomedical applications, in agricultural applications, in consumer applications, in packaging applications or in pharmaceutical applications.

Citation Information

Patent Citations

  • US02010329208A1